Diagnostic Quandary: Salmonella Agbeni Vertebral Osteomyelitis and Epidural Abscess - Ryan K. Dahlberg; Mary Elizabeth Lyvers; Thomas K. Dahlberg (Case Reports in Orthopedics)
Salmonella vertebral discitis/osteomyelitis is a rare manifestation of Salmonella infection. Here, we report a case of a 54-year-old Caucasian male who presented with five weeks of progressively worsening bilateral low back, buttock, and lower extremity pain following an 8-foot fall onto concrete from a ladder. Initial workup following the fall included hip X-ray and MRI of the lumbar spine and revealed only mild lumbar facet arthropathy and moderate left neural foraminal stenosis at L3-L4 without any concomitant hip or spine fracture. The patient’s pain continued to increase in severity over the next several weeks, and he was evaluated by multiple healthcare professionals with no discovered pathology. Approximately 5 weeks following the fall, repeat CT scan and MRI were conducted which then revealed extensive findings of discitis/osteomyelitis at L5–S1 as well as an epidural abscess resulting in severe narrowing of the central spinal canal. Patient underwent emergent decompression laminectomy and discectomy at L5–S1 with evacuation of the epidural abscess. Intraoperative tissue and wound cultures revealed Salmonella enterica serovar Agbeni. The patient recovered well and was discharged on an eight-week regimen of IV ceftriaxone. He has since recovered appropriately with no neurologic deficits. Important takeaways from this case include continuing to work up patients whose pain or condition is not consistent with radiographic findings and the importance of clinical intuition. This case also highlights the use of intraoperative cultures and sensitivities to correctly direct antibiotic management. Lastly, this report adds to the paucity of literature surrounding Salmonella Agbeni-related discitis and epidural abscesses and makes the suggestion that traumatic incidents such as a fall may instigate these infections.